Industrial Revolution 4.0 Regulatory Demand Compliance with Human Resource Practices For Small Medium Manufacturing Sector Enterprises in Malaysia - Murugiah, Suppiah (2024)
The Industrial Revolution evolved from manual labor to the adoption of mechanical, electrical, and electronic technologies over time. However, the electronics industrial development led to digital technology. Germany in 2017 introduced the term industrial revolution 4.0 (IR 4.0), for the engineering process which on implementation can lead to manufacturing efficiency, increased business capacity, quality control, and greater flexibility in operation and production. Since then the basic IR 4.0 technology has evolved from robotics to digital and IOT. As for Malaya/Malaysia, the process of change from manual labor to mechanical, water power and the steam engine was introduced and developed during the tin mining industry in about 1878 that then progressed to Electrical and electronic technology and a well-structured legislation which also provided well structured and seamless training and certification of mostly mechanical and electrical manpower with the relevant skills and talent. [2]IR 4.0 is developing exponentially, and if Malaysia is to meet with the challenges in technology there is a need to develop the manpower of relevant skills and talent. Malaysian government formalized the IR 4.0 transformation through the 4WRD policy which has identified Funding, Infrastructure, Regulations, Skills and Talent and Technology as elements for the IR 4.0 transformation. This thesis is a study on IR 4.0 development in Malaysia with emphasis on the three important elements that is Skills and Talent, technology requirement and more important compliance with Regulatory requirement of the Malaysian government's 4WRD policy. The data collection from 395 sampling from among 70,000 SME industries by Competent Engineer qualified under the Electricity Supply Act 190 and Electricity Regulations 1994. who are actively undertaking technical inspection and audit on a regular basis as a requirement of the Energy Commission? A briefing was given to these Engineers on the requirement of the data collection Forms and the process. Since all these Engineers are experienced in reporting in accordance with the Electricity Regulations 1994 the briefing given was well understood by the Engineers. Theses Engineers we also informed to main ethical values in the data collection industry owners must be informed on the intention and purpose of the data collection which is for academic study and analysis and the personal particulars of the owners and the details of the factory shall remain confidential. It was also explained that result of the survey and report will in fact be useful information for the benefit of the SME industry. Data collection was undertaken and completed without any hindrance. The data so collected was analyzed. The results of the data analysis indicate that the talent and skills, technology and regulatory are in most cases at or below IR3.0.